Relação solo-vegetação em área de cerrado no nordeste do Maranhão, Brasil - Martins, Fredgardson Costa [UNESP] (2014)
The vegetation of the Cerrado biome (Brazilian savanna) is predominantly composed of cerrado physiognomies (cerrado lato sensu). The determining factors on the cerrado physiognomies distribution have been continuously in question, and have been primarily related to gradients of fertility, soil depth, water availability, occurrence of fire, human disturbance and topography. However, there are few studies that have found opposing results or not aligned to these. In this sense, this study was intended to contribute to understanding of these issues, seeking to answer the following questions: Are there floristic and structural differences in vegetation and soil properties faces previously classified as cerradão and cerrado-ralo? Does cerradão occur on soils that are more fertile and/or in mild physical conditions than the cerrado-ralo? For this, we compared physical and chemical soil attributes, as well as floristic patterns (richness and species composition) and structural (density, basal area) of the plant community of three fragments of savanna (cerrado, cerrado degradado and cerrado-ralo) of Northeastern state of Maranhão, located very close to each other in taxonomically identical soils, and therefore subject to similar environmental influences and pedogenic factors. The studied fragments are embedded in a landscape mosaic consisting of remaining areas of cerrado in different levels of degradation. For soil analysis, 49 samples were taken in each fragment in the 0-0.10m soil profile, distributed in a square sampling grid with regular spacing of 15 m. Samples were collected at the point of intersection between the lines of the sampling grid. Sampling was carried out between the months of April and May 2013. Phytosociological survey was carried out in 49 circular plots, in which center the soil sample points were located. A sample of plant material was carried out between the months of January 2012 and May 2013. The ...